2004
DOI: 10.1091/mbc.e03-10-0753
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Peptides as Inhibitors of ErbB Receptor Signaling

Abstract: Receptor tyrosine kinases have a single transmembrane (TM) segment that is usually assumed to play a passive role in ligand-induced dimerization and activation of the receptor. However, mutations within some of these receptors, and recent studies with the epidermal growth factor (EGF) and ErbB2 receptors have indicated that interactions between TM domains do contribute to stabilization of ligand-independent and/or ligand-induced receptor dimerization and activation. One consequence of the importance of these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
1

Year Published

2007
2007
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 37 publications
4
112
1
Order By: Relevance
“…Such a motif has been shown to be important for the dimerization of TM segments of ErbB receptors (Mendrola et al, 2002). Consistently with previous work by Marchesi and colleagues (Bormann et al, 1989), we have also recently demonstrated that synthetic peptides mimicking TM domains are able to inhibit specifically kinase activity and cell signaling by EGF (erbB1) and erbB2 receptors in cultured cells (Bennasroune et al, 2004) as well as chimeric insulin receptors containing these domains (Bennasroune et al, 2005). This inhibition indeed relates to the presence of the GxxxG-type sequence.…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…Such a motif has been shown to be important for the dimerization of TM segments of ErbB receptors (Mendrola et al, 2002). Consistently with previous work by Marchesi and colleagues (Bormann et al, 1989), we have also recently demonstrated that synthetic peptides mimicking TM domains are able to inhibit specifically kinase activity and cell signaling by EGF (erbB1) and erbB2 receptors in cultured cells (Bennasroune et al, 2004) as well as chimeric insulin receptors containing these domains (Bennasroune et al, 2005). This inhibition indeed relates to the presence of the GxxxG-type sequence.…”
Section: Introductionsupporting
confidence: 92%
“…For example, interactions between TM domains contribute to receptor dimerization and thus play a role in the activation of tyrosine kinase receptors of the ErbB family (Mendrola et al, 2002;Bennasroune et al, 2004), the erythropoietin receptor (Constantinescu et al, 2001), alphaIIb integrin (Li et al, 2004), or the T-cell receptor (Teixeiro et al, 2002). These interactions depend on the presence of sequence motifs that govern the packing of the TM helices into homo-or hetero-oligomers (Gordon-Weeks et al, 1989;Arkin, 2002;Curran and Engelman, 2003;Senes et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations